Sistem pengelolaan asuhan keperawatan di poliklinik rawat jalan - Simatupang, Yesi Juniarta; Hariyati, Roro Tutik Sri; Wildani, Andi Amalia (Holistik Jurnal Kesehatan, 2025)
Background: Nursing care management in outpatient units is an important aspect in improving the quality of hospital services. Nursing care is a critical thinking model that is patient-centered and based on a systematic approach starting from assessment, diagnosis, planning, implementation, and evaluation. However, in Indonesia the achievement of nursing care implementation is still not optimal, which is 56.8%. Purpose: To describe the implementation of the nursing care system in outpatient polyclinics. Method: The pilot project carried out included problem identification, problem analysis, determining problem priorities, preparing a Plan of Action (POA), implementation, and evaluation, which was carried out at X hospital Jakarta on September 2-October 2, 2024. Data collection was carried out through interviews, observations, and surveys, then the data was analyzed using strengths, weaknesses, opportunities, and threats (SWOT) analysis. Results: Evaluation showed that 60% of nursing care documentation met quality standards with a 5% increase in knowledge after implementation. Conclusion: Continuous audit improvement and training development are needed to support the implementation of changes. This continuous evaluation is needed to ensure that quality improvements can be maintained and continue to develop. Suggestion: Concrete steps needed are to conduct monthly evaluations of documentation implementation to ensure nursing care is carried out according to standards.   Keywords: Audit; Change; Nursing Care; Outpatient.                 Pendahuluan: Pengelolaan asuhan keperawatan di unit rawat jalan merupakan aspek penting dalam meningkatkan kualitas pelayanan rumah sakit. Asuhan keperawatan adalah model berpikir kritis yang berpusat pada pasien dan didasarkan pada pendekatan sistematis mulai dari pengkajian, penetapan diagnosis, perencanaan, implementasi, dan evaluasi. Namun, di Indonesia pencapaian pelaksanaan asuhan keperawatan masih belum optimal, yaitu sebesar 56.8%. Tujuan: Untuk mendeskripsikan implementasi sistem pengelolaan asuhan keperawatan di poliklinik rawat jalan. Metode: Pilot project terdiri dari identifikasi masalah, analisis masalah, penetapan prioritas masalah, penyusunan Plan of Action (POA), implementasi, dan evaluasi, dilaksanakan di RS X di Jakarta pada tanggal 2 September- 2 Oktober 2024. Data dikumpulkan melalui wawancara, observasi, dan survey, kemudian data dianalisis dengan menggunakan analisis strengths, weaknesses, opportunities, dan threats (SWOT). Hasil: Evaluasi menunjukkan bahwa 60% dokumentasi asuhan keperawatan telah memenuhi standar kualitas dengan peningkatan pengetahuan sebesar 5% setelah implementasi. Simpulan: Audit berkelanjutan dan pengembangan pelatihan perlu ditingkatkan untuk mendukung implementasi perubahan. Evaluasi berkesinambungan ini diperlukan untuk memastikan peningkatan kualitas dapat dipertahankan dan terus berkembang. Saran: Langkah konkret yang diperlukan termasuk evaluasi bulanan terhadap implementasi pendokumentasian untuk memastikan asuhan keperawatan dilakukan sesuai standar.   Kata Kunci: Asuhan Keperawatan; Audit; Perubahan; Rawat Jalan.